207k views
2 votes
Plz help with this solving problem

Plz help with this solving problem-example-1
User Brunoid
by
6.0k points

1 Answer

2 votes
To solve this question, all you would have to do is cross multiply the numerator of the first fraction to the denominator of the second one, likewise do the same for the denominator of the second fraction, multiply it to the numerator of the first fraction.

It should then be:
2(-2x + 6) = 3(X - 2)
-4x + 12 = 3X - 6
12 = 7x - 6
18 = 7x
18/7 = X.

The solution for X is 18/7. You can check if it is correct by plugging in the value of X for the first fraction and see whether it equals the second fraction.
User Taile
by
5.6k points